Optimizing Digipreneurship in the Growth of the Digital Millennial Creative Economy Ecosystem - Anas Abudaqa; Itoimiham Noburu (Pandawan Sejahtera Indonesia, 2025)
This research aims to explore the optimization of digipreneurship in encouraging the growth of the digital creative economy ecosystem among millennials in the digital era. The background of this research emphasizes the economic transformation towards digitalization which offers great opportunities for millennials in the creative sector through technology. Despite this potential, there are several challenges, such as low digital literacy, limited access to technology, and inadequate infrastructure support. The purpose of this research is to understand how digipreneurship contributes to the growth of the creative economy ecosystem by overcoming these challenges. Using a descriptive qualitative method, in depth interviews with creative economy practitioners and secondary data analysis were conducted. The results show that digipreneurship plays an important role in business innovation and market expansion, particularly in fashion, music and design. However, barriers such as limited access to capital and lack of digital skills training are still major obstacles. The conclusion of this study shows that collaboration between the government, educational institutions, and the private sector is essential to strengthen the creative economy ecosystem, increase ac- cess to technology, improve digital literacy, and support the active participation of millennials in the digital economy.